2015
DOI: 10.1016/j.clp.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology and Diagnosis of Invasive Candidiasis Among Premature Infants

Abstract: Invasive candidiasis is a leading infectious cause of morbidity and mortality in premature infants. Improved recognition of modifiable risk factors and antifungal prophylaxis have contributed to the recent decline in the incidence of this infection among infants. Invasive candidiasis typically occurs in the first six weeks of life and presents with non-specific signs of sepsis. Definitive diagnosis relies on growth of Candida in blood culture or cultures from other normally sterile sites, but this may identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 91 publications
5
95
0
4
Order By: Relevance
“…It has been reported that prolonged exposure to broad-spectrum antibiotics not only increases the risk of developing neonatal candidemia [12] but also may be associated with the development of refractory candidemia [13]. The widespread use of antibacterial agents may suppress bacterial flora and increase Candida colonization density [14]. The results of our study were consistent with those of a previous investigation conducted in 11 NICUs, which revealed that broad-spectrum antibacterial agents were commonly used for prophylactic or empiric therapy in China [4].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that prolonged exposure to broad-spectrum antibiotics not only increases the risk of developing neonatal candidemia [12] but also may be associated with the development of refractory candidemia [13]. The widespread use of antibacterial agents may suppress bacterial flora and increase Candida colonization density [14]. The results of our study were consistent with those of a previous investigation conducted in 11 NICUs, which revealed that broad-spectrum antibacterial agents were commonly used for prophylactic or empiric therapy in China [4].…”
Section: Discussionmentioning
confidence: 99%
“…1 Candida sepsis (CS) is a leading infectious cause of morbidity in neonates, in particular among premature infants. 2 The mortality rate from CS is > 40% 3 and it is difficult to diagnose due to its nonspecific signs and symptoms and heterogeneous laboratory data; laboratory findings include thrombocytopenia and elevated C-reactive protein. 4 Prematurity, catheter insertion, use of broad-spectrum antibiotics and mechanic ventilation are major risk factors for CS.…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan çalışmalarda, 3. kuşak sefalosporin veya karbapenemlerin kullanılmasının yanısıra, verilen antibiyotik sayısının ve antibiyotiğin verildiği gün sayısının, H 2 reseptör antagonistlerinin ve parenteral beslenme kullanımının, entübasyonun ve hastanede yatışın uzun olmasının kandidemi için risk faktörleri arasında olduğu belirtilmiştir. Üçüncü kuşak sefalosporin kullanımı en güçlü ve değişti-rilebilir olan risk faktörü olarak belirtilmektedir (16)(17)(18)(19). Gastrik asiditenin gastrointestinal sistemi kandida kolonizasyonuna karşı koruduğu bilinmektedir.…”
Section: Ii) Tıbbi Bakım Verilen Merkezin Uygulamalarıunclassified